How to preach, so people will listen - Nicasio, Lino Evora (Manila Logos Publications, 1993)
Purpose: Discusses the practical aspects of preaching and shares the importance of preaching as a way of communicating the Word of God.
Content/s: Preaching as communication. Preparing the Homily. Delivering the Homily.
Keywords: Preaching -- Handbooks, manuals, etc; Public speaking -- Religious aspects -- Handbooks, manuals, etc